Estudio de factibilidad para la creación de una empresa productora de “Plantillas Ortopédicas” elaborados con materiales amigables con el ambiente (como es “eva” o “stabul”) para niños, niñas de preescolar de la comunidad ambateña, y su comercialización en la provincia del Tungurahua - Criollo Chasi, Ricardo Azael (2015)
The present research had as main objective to develop a feasibility project for the creation of a PRODUCTION COMPANY OF "orthotics" MADE WITH THE ENVIRONMENT FRIENDLY MATERIALS (AS IS "EVA" O "STABUL") FOR CHILDREN PRESCHOOL Nabatene COMMUNITY, AND MARKETING iN THE PROVINCE oF TUNGURAHUA "which gave rise to the thesis topic, which is the first item of work. The thesis project is feasible to do so as this is demonstrated in all studies and contained in the present work. The project is welcome as this is shown by the market study where it was found that there is unmet demand, which was estimated at 9,276 orthotics made with materials friendly to the environment (AS IS "EVA O STABUL" for children of preschool Nabatene community. The technical study it was determined that the company working at 100% capacity could produce 8,320 orthotics made with materials friendly to the environment (AS IS "EVA O STABUL" for children of preschool Nabatene community, however for reasons of market introduction will work with 90% for the first year. According to the organizational study, the new company will be incorporated as a limited liability company. The total investment for the implementation of the new company is 132.726,28, the 77.40% of the total investment, which corresponds to $ 102,726.28 US 6 dollars will be financed with contributions from partners and after searching the most convenient alternative is decided to apply for a loan to Banc de Foment, the lowest interest through its credit lines. The loan will keep the project with the Development Bank constituirá the 22.60% which corresponds to $ 30,000 5-year period to 11% annual interest. The cost of each chair will be $ 78.26 for the first year of life of the project and a retail price of $ 93.92. The breakeven point for the first year of life of the project is 41.88% depending on the installed capacity, and depending on sales will be $ 55,781.14. The financial analysis shows that the project is feasible as the case of van that had a value of $ 7,887.88, the project IRR is 13.25% the sensitivity analysis indicates that the project reaches the point of sensitivity when costs are increased by 27.46% and decrease revenue by 16.14%